The pedagogical from the South: notes to read the existing and emerging - Paola Rubinsztain (Revista Kavilando, 2017)
What does it mean to deepen a critical pedagogical view from the South? What epistemological obstacles are involved, what epistemological obstacles inhibit that perspective? We understand that the construction of a pedagogical perspective implies recognizing "pedagogical" as a field of perspectives and prospects in dispute, where one of the challenges presented is In identifying the traces and discourses of "domesticating pedagogies" that persist and are promoted in the current context and the scenarios that open giving rise to " pedagogies problematizing", this, recovering Freirean terminology.